2006
DOI: 10.1002/adma.200501875
|View full text |Cite
|
Sign up to set email alerts
|

Highly Raman‐Enhancing Substrates Based on Silver Nanoparticle Arrays with Tunable Sub‐10nm Gaps

Abstract: Raman spectroscopy, which is based on the inelastic scattering of photons by chemical entities, has been successfully utilized for the investigation of adsorbed molecules on surfaces, [1][2][3] although the low cross section limits its applications.Surface-enhanced Raman scattering (SERS) has drawn a lot of attention since its discovery in 1974, [4] primarily because it can greatly enhance the normally weak Raman signal and thereby facilitate the convenient identification of the vibrational signatures of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
283
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(293 citation statements)
references
References 28 publications
(27 reference statements)
9
283
1
Order By: Relevance
“…Ag/AAO-SERS substrates consisting of arrays of Ag-nanoparticles partially embedded in AAO nanochannels were fabricated according to the methods described previously 4,21 . To coat Van, substrates (1×1 cm 2 ) were immersed in the various concentration (100 mM-80 µM) of Van hydrochloride (Sigma) aqueous solution for 1 h, and then dried in the air for 12 h. UV-Visible spectrometry (Metertech, SP-8001) was employed to measure the amount of Van in the solution before and after the coating process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag/AAO-SERS substrates consisting of arrays of Ag-nanoparticles partially embedded in AAO nanochannels were fabricated according to the methods described previously 4,21 . To coat Van, substrates (1×1 cm 2 ) were immersed in the various concentration (100 mM-80 µM) of Van hydrochloride (Sigma) aqueous solution for 1 h, and then dried in the air for 12 h. UV-Visible spectrometry (Metertech, SP-8001) was employed to measure the amount of Van in the solution before and after the coating process.…”
Section: Methodsmentioning
confidence: 99%
“…A typical SERSactive substrate consists of arrays of nano-scaled metallic objects, for example, Ag nanoparticles and etch-pits on Ag surfaces, which can sustain surface plasmon polariton resonance and enhance the Raman signal of molecules on or near the substrate [1][2][3] . Recently, a type of SERS-active substrate with uniformly large and highly reproducible Raman-enhancing power has been developed by growing Ag nanoparticles on arrays of anodic aluminum oxide (AAO) nanochannels to take advantage of the sub-10-nm inter-particle gaps, which act as 'hot junctions' for creating the electromagnetic enhancement 4 . The high sensitivity and reproducibility of such a substrate-hereafter referred to as Ag/AAO-SERS substrate-facilitated the use of SERS for chemical/biological sensing applications [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
mentioning
confidence: 99%
“…It has been previously shown that most favorable condition for SERS is observed when plasmonic resonance absorption lies between the exciting laser and Raman emission wavelengths [12]. With the help of the metallic nanoparticles, the enhancement factors up to 10 15 allowing single molecule detection, have been reported [11,[13][14][15][16][17]. Efforts to understand and develop SERS as an analytical tool are dependent on methods for fabricating templates with stable and reproducibly high activities.…”
Section: Introductionmentioning
confidence: 99%
“…As a thumb of rule, the distribution in the length of electrodeposited nanowires in porous template channels increases with the wire length. Therefore, in order to have uniform length MNWs for SERS studies either the deposition time must be shortened, yielding nanodots rather than nanowires [Kartopu et al, 2006;Wang et al, 2006], or the initially long MNWs must be levelled by an appropriate post treatment, such as mechanical polishing [Kartopu et al, 2008b] and ion milling [Sauer et al, 2005]. In the latter case, a chemical etching may be applied to increase the exposed area of nanowires ( Fig.…”
Section: Substrates For Surface-enhanced Raman Scatteringmentioning
confidence: 99%